PEMERINTAH DAN LINGKUNGAN ( STUDI PENANGGULANGAN POLUSI UDARA DI KABUPATEN BENGKALIS TAHUN 2013 ) - Heru Yolanda; Muchid " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study in the background backs by environmental problems occurring in Riau province precisely in Bengkalis in 2013 and which became a severe problem is the problem of air pollution caused by smog from forest fires caused by parties who are not responsible responsibility. Basically a lot of things that can be done to reduce this land arson case made by parties who are not responsible, resulting in increasing the intensity of smog or air pollution in the region Bengkalis. Things to do such as enhanced supervision across the forest area of Riau to procure various outreach programs for the community to be able to preserve hutan.Sebagai footing Theoretically, this study uses the theory of supervision Inu Kencana and Syaufina land and forest fires. research using qualitative methods, while the data collection techniques in doing is to interview and observasi.Sedangkan data analysis using descriptive analysis.The findings indicate dilapanagan fire conditions are not well coordinated, causing a devastating fire that wiped out forests in Bengkalis, thus the supervision of the Government in the District Bengkalis not run with good.This is evident from forest fires occurring continuously menerus.Upaya outage been executed, but because of the many obstacles, handling becomes slow and the effects that arise (such as smog)'ve got to Singapore and Malaysia. A number of the accused as the perpetrator has been processed, although the penalty imposed does not make them jera.Ketidakefektifan handling terlihatdari also continued occurrence of forest fires in Indonesia.